Spatial distribution of modern pollen and fungal spores and their ecological indication in Qinghai Lake on northeastern Tibetan Plateau, China. (November 2022) - Gou, Huating; Wei, Haicheng; Duan, Ronglei; Chen, Tianyuan; Fan, Qishun; Du, Yongsheng; Cao, Xianyong
Highlights: Pollen assemblages show good homogeneity in the Qinghai Lake. Cerealia Poaceae pollen is a sensitive indicator of farming activities. Wind supplying about 10% of extra-regional pollen into lakes on the QTP. Particle size of the fungal spores is an important factor for sorting in the Lake. Abstract: The Qinghai-Tibet Plateau (QTP) – also called the "third pole" – is an ideal area to study the long-term relationship between people and the environment due to its sensitivity to both climate change and anthropogenic activities. Qinghai Lake in the north-eastern QTP is considered a key site to explore this issue. Fossil pollen and fungal spores extracted from lake sediments are effective proxies of palaeoecological evolution and ancient anthropogenic activities, but rely on the modern studies of pollen and fungal spores for an accurate interpretation of the fossil record. In this study, 36 surface-sediment samples from Qinghai Lake were collected from different water depths for pollen and fungal spore analyses to explore the modern characteristics of assemblages and dispersion of pollen and fungal spores. Our results show that the modern pollen assemblages of Qinghai Lake are mainly dominated by Artemisia, Cyperaceae, Poaceae, and Chenopodiaceae, with similar pollen assemblages across the lake, while pollen concentrations show a significant enrichment towards the sedimentary centres of the lake. The modern pollen assemblages reflect the characteristics of the vegetation communities and land use in the basin well. The percentages of Artemisia and Chenopodiaceae pollen are significantly higher in the lake surface-sediment samples than those from topsoil samples of the basin, while percentages of Cyperaceae pollen are lower than those in the topsoil samples. Rivers are an important vector for transporting pollen of intrazonal vegetation, including Cyperaceae, Poaceae, and Hippophae, into Qinghai Lake. Additionally, Cerealia Poaceae pollen (>37 µm) is an effective indicator of farming activities in the Qinghai Lake basin. Fungal spores have higher heterogeneity in their percentages and concentrations from different sampling sites, with Glomus spp. and Delitschia spp. being more abundant near the lakeshore, while other fungal spores, including Sordaria spp., Sporormiella spp. Pleospora spp., Coniochaeta spp., Savoryella spp., and Urocystis sp., having higher percentages and concentrations towards the centre of the lake, with the particle size of the fungal spores being an important factor affecting their transportation and deposition in the lake. This study provides essential data on modern processes and a theoretical basis for accurately interpreting fossil pollen and fungal spore records from lake sediments on the QTP.